THE ROLE OF EXECUTIVE FUNCTIONS IN ENSURING PSYCHOLOGICAL ADAPTATION OF FIRST-GRADERS TO LEARNING IN MODERN CONDITIONS - Talipova Farogat Rustamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The transition to formal schooling represents a critical developmental stage in a child’s life, requiring significant cognitive, emotional, and behavioral adaptation. In modern educational conditions characterized by increased academic demands, digitalization, and rapidly changing learning environments, the role of executive functions becomes particularly significant. Executive functions—including working memory, inhibitory control, cognitive flexibility, planning, and self-regulation—serve as core neuropsychological mechanisms that enable first-graders to manage learning tasks, regulate emotions, and adapt to classroom norms. This study examines the role of executive functions in ensuring the psychological adaptation of first-grade students to school learning. Psychological adaptation is conceptualized as a multidimensional construct encompassing emotional stability, behavioral regulation, academic engagement, and social integration. The paper analyzes theoretical frameworks of executive function development and explores their relationship with successful school adjustment. Special attention is given to how deficits in executive functioning may lead to maladaptive behaviors, learning difficulties, increased anxiety, and reduced academic motivation. The findings suggest that well-developed executive functions significantly contribute to academic readiness, emotional resilience, and positive peer interaction. Furthermore, the study highlights the importance of early assessment and targeted intervention programs aimed at strengthening executive skills in preschool and early primary education. In modern educational contexts, supporting the development of executive functions is a key factor in promoting sustainable psychological adaptation and long-term academic success among first-graders.